Seasonal Current Circulation Patterns in the Waters of the Malacca Strait - Afrianti, Novia Muja; Mubarak, Mubarak; Wibowo, Muhammad Arief (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The Malacca Strait is a water that connects the Indian Ocean and the South China Sea (Pacific Ocean). The Straits of Malacca is the busiest waters because it is filled with activities in and out of ships, fishing activities, ecotourism, and community sea transportation. These activities significantly affect the condition of the waters in the Malacca Strait. Water conditions are greatly affected by oceanographic parameters. One of the most critical parameters is currents. This ocean current is a horizontal movement of water masses influenced by other oceanographic factors. This research was conducted in June - July 2022. This study aimed to determine the pattern of current circulation, direction, and speed of currents as well as sea level during conditions at full moon (highest tide) and new low tide (Lowest tide) each month and every season in the Straits of Malacca. The method used in this research is descriptive quantitative, where numerical data is collected to support the formation of numerical models such as wind, tidal, and bathymetry data. Numerical modeling is a function of the software to determine the pattern of current movement based on the data used. Based on the four seasons (West Season, Transition I, East, and Transition II) at high tide. The highest current speed ranges from 0.02 to 2.07 m/s, while at high tide, the highest current speed ranges from 0.03 to 2.58 m/s.